Comparative efficacy and safety of alternative glucocorticoids regimens in patients with ANCA-associated vasculitis: a systematic review. Issue 2 (25th February 2022) - Xiao, Yingqi; Guyatt, Gordon; Zeng, Linan; RW Jayne, David; A Merkel, Peter; AC Siemieniuk, Reed; Dookie, Jared E; A Buchan, Tayler; Ahmed, Muhammad Muneeb; J Couban, Rachel; Mahr, Alfred; Walsh, Michael
Abstract : Objective: To compare the efficacy and safety of alternative glucocorticoids (GCs) regimens as induction therapy for patients with antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis. Design: Systematic review of randomised controlled trials (RCTs). Data sources: Medline, Embase, Clinicaltrials.gov and Cochrane Central Register of Controlled Trials up to 10 April 2020. Study selection and review methods: RCTs comparing two (or more) different dose regimens of GC in ANCA-associated vasculitis during induction of remission, regardless of other therapies. Pairs of reviewers independently screened records, extracted data and assessed risk of bias. Two reviewers rated certainty of evidence using the Grading of Recommendations Assessment, Development, and Evaluation approach. Results: Of 3912 records identified, the full texts of two records met the eligibility criteria. Due to the heterogeneity of population and dose regimen of GCs between the two trials, we descriptively presented the two trials and did not combine the results using meta-analysis. Compared with the standard-dose regimen, the reduced-dose regimen of GC may reduce death risk difference (RD): from −1.7% to −2.1%, low certainty), while not increasing end-stage kidney disease (ESKD) (RD: from −1.5% to 0.4%, moderate certainty). The reduced-dose regimen probably has an important reduction in serious infections at 1 year (RD: from −12.8% to −5.9%, moderate certainty). Reduced-dose regimen of GCs probably has trivial or no effect in disease remission, relapse or health-related quality of life (moderate to high certainty). Conclusions: The reduced-dose regimen of GC may reduce death at the follow-up of 6 months to longer than 1 year and serious infections while not increasing ESKD. PROSPERO registration number: CRD42020179087.